TEACHER AND PARENT COLLABORATION IN INSTILLING RELIGIOUS RESPONSIBILITY IN STUDENTS AT AN-NIZAM PRIVATE JUNIOR HIGH SCHOOL IN MEDAN - Rizki Nazlia; Ali Imran Sinaga (Pena Cendekia Insani, 2025)
This study investigates the collaboration between teachers and parents in instilling religious responsibility in students at An-Nizam Private Junior High School in Medan. The research used a qualitative approach with a descriptive field study design, involving participant observation and in-depth interviews with teachers and parents. The results show that effective cooperation between teachers and parents significantly enhances students' commitment to religious practices, such as performing Dhuha prayer, congregational Zuhur prayer, and Quran memorization. The study highlights that a strong partnership, facilitated by regular communication and shared responsibilities, is essential for fostering students' religious discipline. This collaboration also strengthens character development, contributing to both academic and spiritual growth. These findings emphasize the need for schools and parents to work together in nurturing students' religious responsibility.